(2S, 6S)- and (2R, 6R)-hydroxynorketamine inhibit the induction of NMDA receptor-dependent LTP at hippocampal CA1 synapses in mice. (September 2020) - Kang, Heather; Park, Pojeong; Han, Muchun; Tidball, Patrick; Georgiou, John; Bortolotto, Zuner A.; Lodge, David; Kaang, Bong-Kiun; Collingridge, Graham L.
The ketamine metabolite (2 R, 6 R )-hydroxynorketamine has been proposed to have rapid and persistent antidepressant actions in rodents, but its mechanism of action is controversial. We have compared the ability of ( R, S )-ketamine with the (2 S, 6 S )- and (2 R, 6 R )-isomers of hydroxynorketamine to affect the induction of N -methyl-d -aspartate receptor–dependent long-term potentiation in the mouse hippocampus. Following pre-incubation of these compounds, we observed a concentration-dependent (1–10 μM) inhibition of long-term potentiation by ketamine and a similar effect of (2 S, 6 S )-hydroxynorketamine. At a concentration of 10 μM, (2 R, 6 R )-hydroxynorketamine also inhibited the induction of long-term potentiation. These findings raise the possibility that inhibition of N -methyl-d -aspartate receptor–mediated synaptic plasticity is a site of action of the hydroxynorketamine metabolites with respect to their rapid and long-lasting antidepressant-like effects.